2018
DOI: 10.1002/srin.201800110
|View full text |Cite
|
Sign up to set email alerts
|

Physical Modeling of Mold Slag Entrainment in Continuous Steel Casting Mold with Consideration the Impact of Mold Powder Layer

Abstract: This paper presents the results of laboratory experiments with the usage of water model of continuous steel casting mold for slabs casting. In laboratory experiments, the liquid slag layer is replaced by silicone oil, whereas mold powder layer is replaced by polypropylene particles. The obtained results has been analyzed using a statistical method based on Taguchi assumptions. Critical casting speeds are determined depending on the viscosity of liquid mold slag. Possible mechanisms of slag entrainment are also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 25 publications
(39 reference statements)
2
5
0
Order By: Relevance
“…(4) The slag drop is transported and dragged deep into the mold, see Figure 7d, and is then finally entrapped by the solidified shell. This entrapment is caused by the vortexing formation in steel, which is usually found near the SEN. A similar phenomenon is also found in Saeedipour's experiment in reference [13], which can also give support to our predicted results. This type of slag entrapment is commonly seen during the injection of steel, indicating that the 1/4 zone, see Figure 1b, is the most likely area where slag entrapment in steel occurs.…”
Section: Validation Of Mathematical Modelsupporting
confidence: 92%
See 2 more Smart Citations
“…(4) The slag drop is transported and dragged deep into the mold, see Figure 7d, and is then finally entrapped by the solidified shell. This entrapment is caused by the vortexing formation in steel, which is usually found near the SEN. A similar phenomenon is also found in Saeedipour's experiment in reference [13], which can also give support to our predicted results. This type of slag entrapment is commonly seen during the injection of steel, indicating that the 1/4 zone, see Figure 1b, is the most likely area where slag entrapment in steel occurs.…”
Section: Validation Of Mathematical Modelsupporting
confidence: 92%
“…Therefore, in addition to the observations stated above, we put forward another simulation work to compare with the experimental result reported by Bielnicki et. al [13] using our three-phase model. It can be seen from Figure 4a that due to the up-recirculation of the water stream, the slag is accumulated near the center of the wide face, thus leading to the fact that the slag layer is rather thin near the narrow wall of the mold.…”
Section: Validation Of Mathematical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Thanks to that, it was possible to check mathematical model used in computer calculations. A physical model of tundish is constructed of glass, on a 2:5 scale (a similar scale of water model was used in another works [31,32]), which has a nominal capacity of 210 L [33]. The hydraulic system and flow meter are used to control the liquid flow in the physical model.…”
Section: Methodsmentioning
confidence: 99%
“…Zhang et al [7] found that the important factor affecting the absorption of slag and inclusions is the surface fluctuation of the velocity, which is caused by the flow field distribution inside the mold. Bielnicki et al [8] found that the conditions of entrained oil are variable and depend on experimental factors. For oils with viscosities of 0.0528 and 0.3748 Pa•s, the presence of mold powder influences the increase in critical water model casting speed.…”
Section: Introductionmentioning
confidence: 99%